Exploring the Singularity Between Google Searches and Suicide Deaths After Celebrity Suicides - Hee Kim, Myung (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The purpose of this study is to suggest the need to strengthen suicide prevention monitoring for the mentally vulnerable by analyzing the specificity and relation between the suicide search volume of Google Trends and the number of suicide deaths according to celebrities’ suicides. The focus of this study is on the high suicide death rates that occurred in specific months between 2019 and 2020. For analysis, data were extracted from raw data and provisional database from deaths due to Specific Cause of Death (intentional self-harm) by month and sex of the Statistics Korea from 2019 to 2020. In addition, Google Trends was analyzed to identify search volume big data based on search terms entered by users along with research reviews. The core of the analysis results is that the number of Google searches based on suicide search terms increased due to the suicide of celebrities, and the number of suicide deaths also increased. In this paper, it is argued that more specific follow-up measures are necessary to prevent further suicide, and as a countermeasure, continuous monitoring of suicide frequency searches in Google Trends after celebrity suicides and special attention are required along with observation of the mentally weak.